Effect of thermal stresses on mechanical properties of structural materials (AH36 and Q235B) in crude oil tanker applications - Odeh, Hussein Hadi; Mohsen, Kadim Karim (Edelweiss Applied Science and Technology, 2025)
This research investigates the effect of heat treatment on the mechanical properties of two structural materials, AH36 and Q235B, with a focus on their hardness, stress-strain behavior, and ductility. The study aims to evaluate how heat treatment influences these properties and to determine the suitability of these materials for different engineering applications. Both materials were subjected to heat treatment, and their mechanical properties, including ultimate stress (σmax), yield stress (σyield), ultimate strain (εmax), and hardness, were evaluated before and after the treatment. The results demonstrated significant changes in both materials as a result of heat treatment. For AH36, the yield stress (σyield) before heat treatment was absent, reflecting a gradual transition from elastic to plastic deformation. After heat treatment, the yield stress increased to 231 MPa, indicating a more uniform microstructure. The ultimate stress (σmax) decreased from 445 MPa to 428 MPa after heat treatment, while the ultimate strain (εmax) increased from 28.45% to 30.80%, showing improved ductility. Hardness values for AH36 decreased from 164 HRB to 154 HRB after heat treatment, reflecting a decrease in strength and an increase in ductility. For Q235B, the yield stress was found to be 434 MPa before heat treatment and decreased to 276 MPa after treatment, indicating a loss in strength and an increase in ductility. The ultimate stress decreased from 432 MPa to 424 MPa, and the ultimate strain remained nearly constant, with only a slight decrease from 20.13% to 20.00%. The hardness values for Q235B dropped from 146 HRB to 128 HRB after heat treatment, indicating a reduction in strength and an increase in material flexibility. The findings highlight that heat treatment leads to a decrease in hardness for both materials, which corresponds to an increase in ductility. The heat-treated AH36 demonstrated improved performance in dynamic loading conditions, while Q235B showed enhanced flexibility and resilience after heat treatment. These results suggest that AH36 is more suited for applications requiring high ductility, while Q235B remains effective for applications requiring higher strength and hardness before heat treatment. In conclusion, this study provides insights into the influence of heat treatment on the mechanical properties of AH36 and Q235B, helping to guide material selection for various engineering applications based on the desired balance between strength, hardness, and ductility. This abstract summarizes the effect of heat treatment on two commonly used structural materials, highlighting key changes in mechanical properties and their implications for practical applications.